EARLY LIVE OVARIAN ECTOPIC GESTATION, CAN THE OVARY BE PRESERVED? : A CASE REPORT: Live ovarian ectopic pregnancy - Adiga, Chaitra; Vinekar, Sripada; Prasad, Mohini N; Mahesh, Deepa (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
Ovarian ectopic gestation is often missed or misdiagnosed and occurs on or within the ovary. Owing to the similar appearances of ovarian pregnancy and corpus luteum cyst, the diagnosis is not straightforward when yolk sac and fetal pole are absent. We hereby report a rare case of early live ectopic gestation in the ovary at 6 weeks of amenorrhea. Ultrasound examination of the pelvis showed, no intrauterine gestation, but a corpus luteum cyst with associated hemoperitoneum and a thick-walled adnexal cyst close to the ovary with fetal node and cardiac activity within confirming ectopic pregnancy. She underwent emergency laparoscopic cyst removal, preserving the ovary and is doing well. Keywords: ectopic pregnancy, laparoscopic cystectomy, live ectopic, ovarian ectopic